Vitamin D supplementation reduced blood inflammatory cytokines expression and improved graft function in kidney transplant recipients - Bai, Yang-Juan; Li, Ya-Mei; Hu, Shu-Meng; Zou, Yuan-Gao; An, Yun-Fei; Wang, Lan-Lan; Shi, Yun-Ying (Frontiers in Immunology, 2023)
Background: Chronic allograft dysfunction(CAD) is the leading cause of graft loss in kidney transplant recipients (KTRs). Inflammatory process is believed to be one of the major contributors to CAD. The aim of this study is to explore the anti-inflammatory effect of vitamin D (VD) supplementation in KTRs and its role in the graft function improvement protection. Methods: A retrospective cohort of 39 KTRs with chronic antibody mediated rejection（CAMR）or stable renal function and a prospective cohort of 42 KTRs treated or untreated with VD were enrolled.Serum levels of vitamin D metabolism and serum inflammatory cytokines, renal graft function,and routine blood biomarkers were tested and dynamically tracked within 12 months post-transplant. Results: Compared with the stable group, the CAMR group exhibited significantly elevated serum levels of inflammatory cytokines IL-1β, IFN-γ, IL-2, IL-10, IP-10 , and HMGB1 (P <0.05). The supplementation of vitamin D effectively increased the serum concentration of vitamin D in kidney transplant recipients (KTRs) in the treated group. During the course of treatment, the treated group exhibited a gradual increase in eGFR levels, which were significantly higher than those observed in the untreated group at 12 months post-transplant (p<0.05). Notably, as eGFR improved, there was a significant decrease in levels of IL-1β, IFN-γ, IL-2, IL-10, IP-10 and HMGB1 in the treated group compared to the untreated group (P<0.05). Conclusion This study confirmed that immune-inflammation is a crucial factor in the development of CAD in KTRs.VD deficiency impairs its anti-inflammatory activity. By assisting in the regulation of excessive immune inflammation and restoration of immune homeostasis, effective VD supplementation contributes to protection and maintenance of graft function in KTRs.